Bacterial composition changes and volatile compounds during the fermentation of shrimp paste: Dynamic changes of microbial communities and flavor composition. (October 2021) - Che, Hongxia; Yu, Jing; Sun, Jinyuan; Lu, Kuan; Xie, Wancui
Abstract: Shrimp paste is a traditional Chinese fermented food. To understand the relationship between microbial composition and flavor formation during the fermentation process, high-throughput sequencing and solid phase microextraction-gas chromatography technology were used to measure the dynamic changes of microbial communities and flavor composition. The bidirectional orthogonal partial least squares model was used to establish the correlation between volatile components and bacterial composition. A higher relative abundance of dominant genera including Salimicrobium, Lentibacillus, Lactobacillus, and Tetragenococcus was found throughout the fermentation period. Totally, 77 types of volatile compounds were detected, including nitrogen-containing compounds, aldehydes, alcohols, esters, and ketones. Alcohols (1-octanol, phenylethyl alcohol, and 2-butyl-1-octanol) and nitrogen-containing compounds (3-methyl-pyrazine and 2, 5-dimethyl pyrazine) showed a positive correlation with Salimicrobium, Tetragenococcus, and Lactobacillus . Some aldehydes (isovaleraldehyde and 3-methylbutanal), ketones and nitrogenous compounds (trimethylamine and oxazole) were strongly negatively correlated with Lactobacillus, Salimicrobium, and Tetragenococcus. A correlation was established between the important microbes and the main flavor compounds. These results may provide a basis for the quality control and flavor compounds change mechanisms in the fermentation process of shrimp paste, which may be helpful to formulate standardized parameters and obtain constant quality products.